1997
DOI: 10.1108/13565369710368151
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Thin‐film Barrier Metals for Eutectic Solder Bumps

Abstract: This paper describes effective thin‐film structure barrier metals for use as eutectic solder bumps. Shear strength and bump interconnection resistance were evaluated. The mutual diffusion in metals was investigated. Barrier metal structures —Cu/Ti,Ni/Ti and Cu/Cr—were evaluated after ageing. The Ni/Ti structure has good reliability according to ageing test results. Pd is used for improvement of solder wettability and as an oxidisation barrier. Consequently, it was concluded that a thin‐film Pd/Ni/ Ti barrier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our investigation concluded that the thin f i structure has a good thermal stability at the interface of solder bumps and A1 pads [6] [7]. Therefore, we choose this structure for the barrier metal.…”
Section: Discussionmentioning
confidence: 95%
“…Our investigation concluded that the thin f i structure has a good thermal stability at the interface of solder bumps and A1 pads [6] [7]. Therefore, we choose this structure for the barrier metal.…”
Section: Discussionmentioning
confidence: 95%
“…Eutectic solder flip chip has some advantages such as good bonding yield by good wettability and applicability to low cost substrate like warped substrate or typical organic substrate which can not endure high temperature. Eutectic solder flip chip interconnection technology has been developed in Toshiba and some reliability and packaging issue were reported [5], [6]. Estimation of capillary action in underfilling process has also been in progress [7].…”
Section: Introductionmentioning
confidence: 99%